Wage Standards for Abdi Dalem of Kotagede Royal Cemetery and Cultural Meaning of Voluntarism and Dedication - Shalihah, Fithriatus (Udayana Journal of Law and Culture, 2024)
Yogyakarta's special status was recognized long before Indonesia's independence as a cultural heritage site. One of the privileges of Yogyakarta is that it maintains its cultural legitimacy amidst increasingly modern developments. This paper aims to discuss whether (or not) the practice of waging for abdi dalem at the Kotagede Royal Cemetery is compatible with Indonesian Employment Law. It applies empirical legal research, which collects primary and secondary data sources. It suggests that abdi dalem, who works at the Kotagede Royal Cemetery, receives kekucah (wages) below the minimum standard according to regional regulations. However, the serat kekancingan, a decree issued by the Yogyakarta Sultanate that explains the status of abdi dalem, must not be interpreted as conflicting with Indonesian employment law, particularly regulations determining the minimum wages. This research also found that abdi dalem tends not to protest this status quo because they uphold a live philosophy of Nrimo ing pandum. Therefore, abdi dalem accepts all tasks assigned sincerely by the Sultan without expecting anything in return. They firmly believe that serving at the Kotagede Royal Cemetery will bring abundant blessings and peace from God through the Sultan.